2006
DOI: 10.1097/01.ajp.0000210931.20322.da
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Cotreatment With Dextromethorphan and Ketorolac Provides an Enhancement of Pain Relief After Laparoscopic-assisted Vaginal Hysterectomy

Abstract: Preoperative treatment with both DM and ketorolac diminish postoperative pain. Our results suggest that the N-methyl-D-aspartate antagonist-DM and the nonsteroidal anti-inflammatory drugs-ketorolac cotreatment provide an enhancement of analgesia for postoperative pain management in patients after LAVH surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…All included trials were conducted in adult populations aged 18 years or older, and 1 study was conducted specifically in a geriatric population over 65 years of age. 19 All studies were conducted in the surgical setting, and common surgeries in the trials reviewed included gynecologic surgery/cesarean delivery (n = 15), 12,13,18,[20][21][22][23][24][25][26] orthopedic/arthroscopic surgery (n = 10), 11,14,19,[27][28][29][30][31][32][33] and spinal surgery (n = 4). [34][35][36][37] Findings from individual NSAIDs are presented below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All included trials were conducted in adult populations aged 18 years or older, and 1 study was conducted specifically in a geriatric population over 65 years of age. 19 All studies were conducted in the surgical setting, and common surgeries in the trials reviewed included gynecologic surgery/cesarean delivery (n = 15), 12,13,18,[20][21][22][23][24][25][26] orthopedic/arthroscopic surgery (n = 10), 11,14,19,[27][28][29][30][31][32][33] and spinal surgery (n = 4). [34][35][36][37] Findings from individual NSAIDs are presented below.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies examined ketorolac at various doses as an opioid-sparing strategy, and results from these studies are summarized in Table 2. 13,16,21,25,31,39,40 Each study evaluated ketorolac treatment against a control group that did not receive the NSAID, and all of these studies reported significant opioid-sparing effects with ketorolac. Opioidsparing effects were determined versus a background of PCA opioids in 6 of the 7 studies, 13,21,25,31,39,40 and versus morphine titrated to pain level as rescue medication in the remaining study.…”
Section: Ketorolacmentioning
confidence: 99%
“…To obtain a more complete description of analgesia effectiveness, [30][31][32] both current pain at rest [visual analog scale at rest (VASr)] and after a voluntary cough [visual analog scale after coughing (VASi)] were assessed hourly for the first 4 hours after the start of PCA (T0). Subsequently, they were performed every 4 hours for the next 20 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Yeh et al [24] reported the efficacy of intramuscularly administered dextromethorphan (40 mg) prior to surgical incision and suggested that postoperative controlled epidural analgesia (PCEA) consisting of ropivacaine and morphine could be enhanced by a single administration of dextromethorphan before surgery. The same research group demonstrated that the effect of dextromethorphan and ketorolac after vaginal hysterectomy was rescued by PCA morphine [25]. After single administration, the effect of dextromethorphan lasted 24 h, probably because the metabolism of dextromethorphan, or the effect of metabolites of dextrophan-potent NMDA antagonists, lasts only 24 h. In both studies, epidural or intravenous morphine had been administered and epidural local anesthetics or NSAIDs were used.…”
Section: Problems In the Study Of Dextromethorphan: A Comparison Withmentioning
confidence: 99%